Thromboelastometric analysis of the risk factors for return of spontaneous circulation in adult patients with out-of-hospital cardiac arrest - Koami, Hiroyuki; Sakamoto, Yuichiro; Sakurai, Ryota; Ohta, Miho; Imahase, Hisashi; Yahata, Mayuko; Umeka, Mitsuru; Miike, Toru; Nagashima, Futoshi; Iwamura, Takashi; Yamada, Kosuke Chris; Inoue, Satoshi (PloS one, 2017)
It is well known that coagulopathy is observed in patients with out-of-hospital cardiac arrest (OHCA). Thrombolytic therapy for those patients has been controversial until now. The purpose of this study was to identify a significant predictor for return of spontaneous circulation (ROSC) of OHCA patients in the emergency department (ED) using whole blood viscoelastic testing. Adult non-trauma OHCA patients transported to our hospital that underwent thromboelastometry (ROTEM) during cardiopulmonary resuscitation between January 2013 and December 2015 were enrolled in this study. We divided patients into two groups based on the presence or absence of ROSC, and performed statistical analysis utilizing patient characteristics, prehospital data, laboratory data, and ROTEM data. Seventy-five patients were enrolled. The ROSC group and non-ROSC group included 23 and 52 patients, respectively. The logistic regression analysis, utilizing significant parameters by univariate analysis, demonstrated that lactate level [odds ratio (OR) 0.880, 95% confidence interval (CI) 0.785-0.986, p = 0.028] and A30 of EXTEM test [OR 1.039, 95% CI 1.010-1.070, p = 0.009] were independent risk factors for ROSC. The cut-off values of lactate and A30 in EXTEM were 12.0 mmol/L and A 48.0 mm, respectively. We defined a positive prediction for ROSC if the patient presented lower lactate level (<12.0 mmol/L) and higher A30 of EXTEM (≥48.0 mm) with high specificity (94.7%) and accuracy (75.0%). The present study showed that lactate level and ROTEM parameter of clot firmness were reliable predictors of ROSC in the ED for adult patients with OHCA.